1990
DOI: 10.1161/01.cir.81.4.1182
|View full text |Cite
|
Sign up to set email alerts
|

111In platelet imaging of left ventricular thrombi. Predictive value for systemic emboli.

Abstract: To determine whether a positive indium 111 platelet image for a left ventricular thrombus, which indicates ongoing thrombogenic activity, predicts an increased risk of systemic embolization, we compared the embolic rate in 34 patients with positive "'1In platelet images with that in 69 patients with negative images during a mean follow-up of 38±31 (+SD) months after platelet imaging. The positive and negative image groups were similar with respect to age (59± 11 vs. 62± 10 years), prevalence of previous infarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…w42 In indium-111 platelet imaging studies most thrombi, regardless of age, have been observed to have externally detectable ongoing platelet accumulation, indicating continued surface activity. 20 The European guidelines recommend vitamin K antagonist for at least 3e6 months, while the American guidelines recommend indefinite treatment in patients without increased risk of bleeding.…”
Section: Vitamin K Antagonistmentioning
confidence: 99%
“…w42 In indium-111 platelet imaging studies most thrombi, regardless of age, have been observed to have externally detectable ongoing platelet accumulation, indicating continued surface activity. 20 The European guidelines recommend vitamin K antagonist for at least 3e6 months, while the American guidelines recommend indefinite treatment in patients without increased risk of bleeding.…”
Section: Vitamin K Antagonistmentioning
confidence: 99%
“…The method proved to be sensitive for the detection of left ventricular thrombi in humans, 49,50 and was predictive of the occurrence of systemic emboli. 51 Of note, the uptake of 111 In-labeled platelets declined with time in chronic thrombi, owing to a decreased platelet incorporation. 52,53 In infective endocarditis, the technique provided the means of directly observing the pathogenic role of blood cellular components within the vegetation.…”
Section: Vegetations Of Infective Endocarditismentioning
confidence: 99%
“…The variability in T2G1s uptake shown in the histological sections is reflected in the well-counting data. Figure 3 shows the results from a single dog of a well-counted femoral thrombus sectioned into 4. Bar graphs of artery-or thrombus-to-blood ratios (mean ±SEM) shown for control artery (n = 13), injured artery (n=23), and thrombus (n=23), using average uptake for all 5-mm segments or segment with maximal uptake of T2GJs.…”
Section: Histologymentioning
confidence: 99%
“…The thrombi weighed 218±+140 mg. Antibody uptake in the thrombi was patchy, and the thrombi were closely adherent to the injured arterial wall. In the segment with maximal ex vivo antibody uptake, the ratio of control artery to blood counts/g/sec was 0.65 ±0.46, the injured artery-to-blood ratio was 2.35± 1.01 (p<0.0001 versus control), and the thrombus-to-blood ratio was 4 A novel imaging approach is the use of specific antibodies directed at various thrombus components. One such antibody, T2G1s, reacts specifically with the first seven amino acids of the fibrin fl-chain.5 A similar antifibrin antibody, 59D8, reacts with the same por-tion of the /3-chain.…”
mentioning
confidence: 98%